Activation of Sales of Belarusian Enterprises Based on the Development of Approaches to the Classification of Electronic Trading Platforms - T. A. Asipovich (Цифровая трансформация, 2024)
The article presents the results of a comparative analysis of existing electronic trading platforms in the world. It characterizes business models of cooperation between sellers and operators of such Internet platforms in the field of marketing research, sales methods, promotion tools, forms of payment and logistics. Based on modern trends in the use of marketplace functionality, a number of classification criteria are proposed. Among them: the range of the object of purchase and sale, the possibility of resale of goods, the region of location of buyers, the choice of the organizational and legal status of the marketplace, the participation of the marketplace in the process of selling goods, business models of working with the marketplace, payment methods, the possibility of integrating the marketplace with other Internet resources, the conditions for registering buyers and sellers. The obstacles to activating sales of Belarusian enterprises on marketplaces are identified, recommendations for their elimination are offered.